The Reality of Confidi: Delinquency Rate and Political Decisions - Rovera, Cristina (Insights into Economics and Management Vol. 8, 2021)
This study is focused on the Italian confidi, the financial institutions placed in an intermediate position between lenders and borrowers, because they offer guarantees care of banks to the associated SMEs. During the last years we can observe an important reduction in the number of confidi. The main aim of the research is to look for an explication of the phenomenon. Why has the number of confidi reduced? Does it depend on their delinquency rate? Or on the Italian Government policies? To determine the responsible factors the study realizes both a quantitative and a qualitative analysis. The first one is on a large representative panel (99 confidi). The regression model shows that the difficulties in credit collections essentially depend to the economic crisis and to the bad management of the organizations. But the delinquency rate is not the only explanatory factor. The second cause depends on decision-making policies. The last interventions put a stop to the growth of confidi, forcing those that are not operational or do not comply with regulatory requirements to close.